Fakt versus Fake: Kommunikative Strategien in Faktenchecks auf Instagram - Stelter , Judith (Linguistik Online, 2024)
The COVID-19 pandemic has caused uncertainty in society and thus created a breeding ground for fake news. In social media in particular, targeted disinformation was and is practiced in order to emotionalize, confuse and manipulate users to achieve political and economic goals. In keeping with its educational and orienting function and in order to curb the spread of fake news, the established news magazine DER SPIEGEL carries out so-called fact checks and publishes the results on the social network Instagram. Although the text type “fact check” is considered young and poorly defined, its importance in socially uncertain times and its potential for a quick, safe and educational function are clear. In order to approach the text type “fact check” specifically in a social media environment, a selected corpus of 12 Instagram posts from @spiegelmagazin in the period between March and May 2020 will be examined using a multimodal, qualitative discourse analysis. Taking an inductive perspective, we ask which strategic text-image strategies can be found in the Instagram posts, which communicative functions are fulfilled and which overarching intentions should be taken into account. The study itself is intended to offer a first approach to the text type “fact check” and open the view to further, relevant questions.